Chrysoperla externa (Hagen) regulatory capacity against whtefly Trialeurodes vaporariorum (Westwood) in tomato under glasshouse conditions. - Castro-Lopez, Mayerly Alejandra; Martinez-Osorio, John Wilson (Universidad Pedagógica y Tecnológica de Colombia, 2016)
Trialeurodes vaporariorum Westwood (Hemiptera: Aleyrodidae) is one of the main limiting factors disturbing tomato (Solanum lycopersicum) crop, due to its direct and indirect effects in the fruit’s production system. This pest management has been focused on excessive chemical products, mostly without good results. This study aim was to evaluate under glasshouse conditions, the regulatory capacity of Chrysoperla externa Hagen (Neuroptera: Chrysopidae) against white fly in tomato. In tomato plants infested with T. vaporariorum, individuals of Chrysoperla externa were added at different levels, which consisted in 80, 160 and 240 individuals in larval stage per plant; also a control without the predator was used. To asses the experiment, a complete randomized design was used under glasshouse conditions (mean temperature of20 °C and relative humidity of 60 %). Significant statistical differences were observed between the predator densities with 35, 52 and 53 infestation percentages of T. vaporariorum (after 4 weeks), corresponding to the liberation of 240, 160 and 80 individuals per plant, respectively. Regarding with tomato, it was obsewed a lower plant height increase, plus smaller branches and less number per plant with the control, than the treatments with C. externa predator presence.